Quality management of the bamboo resource and its contribution to environmental conservation in Malaysia - Mohamed, Azmy; Hall, J. B.; Sulaiman, Othman; Wahab, Razak; Wan Abd Kadir, Wan Rashidah (Emerald Group Publishing Limited, 2007)
Purpose – The aim of this study was to contribute towards the systematic management of the natural stand bamboo resource at Nami, Kedah, Malaysia and to improve the forest environment rather than leaving it neglected and unmanaged. In addition, the study examines the commercial value of the abundant bamboo culms for a sustained industry in Malaysia.